2022
DOI: 10.3390/jcm11071921
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MRI in the Genitourinary System

Abstract: Diffusion weighted imaging (DWI) constitutes a major functional parameter performed in Magnetic Resonance Imaging (MRI). The DW sequence is performed by acquiring a set of native images described by their b-values, each b-value representing the strength of the diffusion MR gradients specific to that sequence. By fitting the data with models describing the motion of water in tissue, an apparent diffusion coefficient (ADC) map is built and allows the assessment of water mobility inside the tissue. The high cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 137 publications
(161 reference statements)
0
5
0
Order By: Relevance
“…Therefore, it is essential to search for adequate predictive markers that can be easily performed in clinical practice to identify patients who can maximally benefit from treatment. Previous studies have demonstrated that radiomic information from MRI can improve the efficiency of precise diagnosis by leveraging high-resolution morphological images and providing various functional information, such as tissue oxygenation, perfusion, or diffusion (35)(36)(37)(38). In addition, recent studies have demonstrated that radiomics information from MRI can be used to predict the treatment response to platinum, risk of recurrence, and residual disease in patients with ovarian HGSC (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to search for adequate predictive markers that can be easily performed in clinical practice to identify patients who can maximally benefit from treatment. Previous studies have demonstrated that radiomic information from MRI can improve the efficiency of precise diagnosis by leveraging high-resolution morphological images and providing various functional information, such as tissue oxygenation, perfusion, or diffusion (35)(36)(37)(38). In addition, recent studies have demonstrated that radiomics information from MRI can be used to predict the treatment response to platinum, risk of recurrence, and residual disease in patients with ovarian HGSC (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Together with the incessant proliferation of tumor cells, this results in the extrusion and deformation of the extracellular space. Consequently, the movement of water molecules within the tumor becomes restricted, leading to a decrease in ADC values during DWI scans [14][15][16]. This phenomenon serves as the pathological foundation for the diagnostic utility of DWI in the identification of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative parameter that integrates both the random diffusion and directional movement of water is the apparent diffusion coefficient (ADC). The ADC provides insight into the extent of water diffusion in extracellular/extravascular spaces and capillary perfusion [31,60]. Both preclinical and clinical studies have demonstrated lower renal ADC values in dysfunctional renal transplants and native renal pathologies.…”
Section: Diffusion-weighted Magnetic Resonance Imagingmentioning
confidence: 99%